Menumbuhkan Budaya Menabung Sejak Dini: Program 'Giat Menabung, Celengan Ceria' di TK Pertiwi 1 Koripan - Ratih Kurnia; Melansari Siti Nurtiara; Ahmad Baihaqi Saputra; Gufron Amirullah; Khusniyati Masykuroh (CV. ALIM'SPUBLISHING, 2025)
Program